Respuesta :

Answer:

[tex]x = \frac{7}{2}[/tex]

Step-by-step explanation:

[tex]6^{x-1} = 36 \sqrt6\\\\6^{x-1} = 6^2 \times 6^{\frac{1}{2}}\\\\6^{x-1} = 6^{2 + \frac{1}{2} }[/tex]                        [tex][ \ a^x \times a^ y = a^{x+ y} \ ][/tex]

[tex]x - 1 = 2 + \frac{1}{2}[/tex]                          [tex][ \ b^x = b^y => x = y \ ][/tex]

[tex]x = 2 + \frac{1}{2} + 1\\\\x = 3 + \frac{1}{2} \\\\x = \frac{6+ 1}{2} \\\\x = \frac{7}{2}[/tex]

Answer:

x = 3.5

Step-by-step explanation

       

Using the rules of exponents

[tex]a^{m}[/tex] × [tex]a^{n}[/tex] ⇔ [tex]a^{(m+n)}[/tex] and [tex]\sqrt{a}[/tex] = [tex]a^{\frac{1}{2} }[/tex]

Then

36[tex]\sqrt{6}[/tex] = 6² × [tex]6^{\frac{1}{2} }[/tex] = [tex]6^{(2+0.5)}[/tex] = [tex]6^{2.5}[/tex]

Thus

[tex]6^{x-1}[/tex] = [tex]6^{2.5}[/tex]

Since the bases on both sides are equal, both 6, equate the exponents

x - 1 = 2.5 ( add 1 to both sides )

x = 3.5

ACCESS MORE